Comparative Stylistic Analysis on Soundtrack Anastasia Selected Songs Lyrics - Chintia Handayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Problem of the research is What Comparative Stylistic Elements are found on selected songs of soundtrack Anastasia movie and What iss Comparative Stylistic meanings used on selected songs of soundtrack Anastasia movie lyrics. The objectives of the research are to find out the existence of Comparative Stylistic Elements that are found on soundtrack Anastasia movie songs. To analyze the comparative stylistic meanings that are used on soundtrack Anastasia movie songs. The researcher found out the data from At the beginning song, there are 3 metaphors, 3 personifications, 2 prelopsis., In the dark of the night song, the researcher found out 2 depersonifications, 4 allegory, 4 prelopsis, 3 epanorthosis. So, the total from the two songs are 21 data